2013
DOI: 10.1177/0038040713494225
|View full text |Cite
|
Sign up to set email alerts
|

School Violent Crime and Academic Achievement in Chicago

Abstract: Educational outcomes vary dramatically across schools in the United States. Many under-performing schools, especially in Chicago, also deal with high levels of violent crime on school grounds. Exposure to this type of frequent violence may be an important factor shaping already disadvantaged students’ educational experiences. However, estimating the effect of school violence on learning is difficult due to potential selection bias and the confounding of other school-level problems. Using detailed crime data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 40 publications
2
45
0
6
Order By: Relevance
“…Interactions with each year dummy variable show very similar results, but are much more difficult to interpret and do not fit the data as well as the linear interactions. Similar models were used in Keels, Burdick-Will, and Keene (2013) to test the relationship between gentrification and school-level improvement over a decade long period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions with each year dummy variable show very similar results, but are much more difficult to interpret and do not fit the data as well as the linear interactions. Similar models were used in Keels, Burdick-Will, and Keene (2013) to test the relationship between gentrification and school-level improvement over a decade long period.…”
Section: Methodsmentioning
confidence: 99%
“…Even as objective violent crime rates go up and down and residents move in and out, the reputation for risk in an area remains relatively stable (Sampson 2012). For example, despite dramatic changes in the violent crime rate on school grounds, students’ reports of perceived school safety change very little from year to year (Burdick-Will 2013). This suggests that the patterns of social interaction formed in early childhood may be difficult to break.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, from the epidemiological point of view, it would be possible to say that the Mexican middle school students might be at risk to develop future academic, psychologic or behavioral problems because of the negative perception of the school climate dimensions (Zullig, Collins, Ghani, Patton, Huebner, & Ajamie, 2014;Burdick, 2013;Esselmont, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It represents an important construct in school life because it stablishes the socially acceptable behavior in the school, shaping the interactions between the school members (students, teachers and parents) and influencing its development in different aspects. In the student's case, several studies had found that school climate perception plays an important role on their academic, psychological and behavioral development (Dotterer & Lowe, 2011;Berger, Álamos, Milicic, & Alcalay, 2013;Iachini, Buettner, Anderson, & Reno, 2013;Burdick, 2013;Esselmont, 2014). For the staff, it affects topics such as work engagement and satisfaction, along with the perceived occupational health (Gregory, Cornell, & Fan, 2012;Blömeke & Klein, 2013;Song, Kim, Chai, & Bae, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In communities, perceived safety affects outdoor physical activity and recreation. In individuals, negative safety perceptions can increase acute or chronic stress and/or anxiety (Burdick-Will, 2013). Overall, feeling unsafe in one's community can create numerous barriers to healthy living.…”
Section: Percentage Of Middle and High School Students Reporting Feelmentioning
confidence: 99%